Going beyond loaning books to loaning technologies : a practical guide for librarians - Sander, Janelle, 1982-; Mestre, Lori; Kurt, Eric, 1979- (Practical guides for librarians ;, 2015)
Providing library users with actual pieces of technological equipment that they can borrow is a continuously expanding service at many libraries, especially as faculty and teachers require multimodal projects. For some libraries, loanable technology may include calculators, gaming devices, headphones, e-readers, laptops, and tablets. Increasingly though, there is also demand for all types of cameras, lighting, voice recorders, microphones, external storage devices, projectors, peripherals and converters, among hundreds of possibilities. Based on their successful program at a large research institution, the authors provide a practical manual, complete with examples, forms, and templates that cover all aspects of establishing and maintaining a loanable technology program.